Effect of 10.6 μm laser moxibustion on inflammation in diabetic peripheral neuropathy rats - Yin, Yue; Wang, Lina; Zhao, Ling; Lin, Lin; Shen, Xueyong (Frontiers in Endocrinology, 2023)
Diabetic peripheral neuropathy (DPN) is the main cause of disability in diabetes patients but the efficacy of available drugs is poor. Moxibustion is an adjunctive treatment for DPN that can reduce symptoms. The peak value of the far infrared wavelength of 10.6 μm laser moxibustion is close to the infrared radiation spectrum of traditional moxibustion. Its effect is similar to that of moxibustion and does not cause pain, infection or produce irritating smoke. Twenty-four male SD rats were divided into control (Con), DPN, laser moxibustion (LM), and dithiocarbamate pyrrolidine (PDTC) groups (n=6/group). The DPN, LM and PDTC group rats were intraperitoneally injected with 1% streptozotocin (STZ) to induce a model of DPN. LM group rats were irradiated with a laser at bilateral ST36 acupoints for 15 min, once every other day, for 14 days. PDTC group rats were intraperitoneally injected with PDTC once a day. Body weight, blood glucose, and paw withdrawal mechanical threshold (PWMT) were measured and laser speckle imaging (LSI) performed before and after modeling and at 1 and 2 weeks after intervention. Two weeks after intervention, changes in serum interleukin 1β (IL1β), interleukin 6 (IL6), tumor necrosis factor α (TNFα) and nerve growth factor (NGF) were analyzed, and the abundance of NF-κB and IκB-α proteins and levels of NF-κB and IκB-α mRNAs in the sciatic nerve were observed. The results showed that 10.6 μm laser moxibustion can relieve pain, improve microcirculation, and alleviate inflammation in DPN rats, possibly via the NF-κB inflammatory pathway.